1991
DOI: 10.1093/ptj/71.2.98
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Measurements of Cervical Spine Range of Motion—Comparison of Three Methods

Abstract: To determine reliabilities within and between persons measuring cervical active range of motion (AROM) three methods were examined: use of a cervical-range-of-motion (CROM) instrument, use of a universal goniometer (UG), and visual estimation (VE). Measurements were made on 60 patients with orthopedic disorders of the cervical spine who were divided into three groups of 20 subjects each. All subjects were tested in a standardized seated position using operationally defined goniometric placements and nongoniome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
242
4
10

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(267 citation statements)
references
References 8 publications
11
242
4
10
Order By: Relevance
“…The rotation inclinometer has a magnetic needle with its accuracy reinforced by magnets placed over the subject's shoulders. Several studies have reported that the CROM device is a reliable 4,11,23,39 and valid 13,25,[32][33][34] instrument for assessing active cervical ROM, including rotation. 11,34 Rotation movement of the cervical spine was specifically assessed because of the finding in a previous study of patients with neck pain that cervical rotation ROM increased significantly when the scapulae were passively elevated.…”
Section: Methodsmentioning
confidence: 99%
“…The rotation inclinometer has a magnetic needle with its accuracy reinforced by magnets placed over the subject's shoulders. Several studies have reported that the CROM device is a reliable 4,11,23,39 and valid 13,25,[32][33][34] instrument for assessing active cervical ROM, including rotation. 11,34 Rotation movement of the cervical spine was specifically assessed because of the finding in a previous study of patients with neck pain that cervical rotation ROM increased significantly when the scapulae were passively elevated.…”
Section: Methodsmentioning
confidence: 99%
“…The reduced motion may reflect a mechanical problem with the specific joint caused by stroke. The range of motion is a very useful indicator to quantify the performance of movement, and an important factor in most impairment guides as well [19,20]. In this paper, the mean value of joint angle during isometric contraction was defined in the range of motion as Eq.…”
Section: Range Of Motionmentioning
confidence: 99%
“…The neurologic findings on exam were highly correlated to the pathology found during surgery according to Yoss et al [14]. Cervical range of motion is often tested in patients who complain of neck pain and radicular symptoms [15]. Patients often have impairment in their range of motion and limitation in their function.…”
Section: Resultsmentioning
confidence: 93%